Sexual Violence as a War Weapon in Conflict Zones: Palestinian Women's Experience Visiting Loved Ones in Prisons and Jails. Issue 2 (May 2021) - Al Issa, Ferdoos Abed-Rabo; Beck, Elizabeth
At present, there are about 4, 500 Palestinians detained in Israeli prisons and jails. This study explores Palestinian women's experiences with sexual violence by prison personnel as they visit their detained loved ones. In interviews with 20 participants, the prevalence of, type of, and reaction to sexual violence were explored. Nineteen of the 20 participants stated that they experienced some sort of unwanted verbal and nonverbal sexual comments or gestures, forced nudity, or forced touching by prison personnel. The women talked about how the experiences have harmed them as well as the strategies that they use to overcome their experiences. The findings are contextualized within international law and describe the implications of sexual violence within a culture that links modesty with religious beliefs and honor. The implications of as well as strategies to address sexual violence are discussed at micro-, mezzo, and macro level.